Hepatitis B virus‐regulated growth of liver cancer cells occurs through the microRNA‐340‐5p‐activating transcription factor 7‐heat shock protein A member 1B axis. Issue 5 (11th April 2019) - Song, Feifei; Wei, Mingcong; Wang, Jingwen; Liu, Yang; Guo, Mingxiong; Li, Xiaolu; Luo, Jun; Zhou, Junying; Wang, Min; Guo, Deyin; Chen, Lang; Sun, Guihong
Abstract : Hepatocellular carcinoma (HCC) is a common cancer with poor prognosis. Hepatitis B virus (HBV) is one of the leading causes of HCC, but the precise mechanisms by which this infection promotes cancer development are not fully understood. Recently, miR‐340‐5p, a microRNA (miRNA) that has been identified as a cancer suppressor gene, was found to inhibit the migration and invasion of liver cancer cells. However, the effect of miR‐340‐5p on cell proliferation and apoptosis in HBV‐associated HCC remains unknown. In our study, we show that miR‐340‐5p plays an important role during HBV infection and hepatocellular carcinoma development. Specifically, this miRNA directly binds to the mRNA encoding activating transcription factor 7 (ATF7), a protein that both promotes cell proliferation and suppresses apoptosis through its interaction with heat shock protein A member 1B (HSPA1B). We further found that miR‐340‐5p is downregulated by HBV, which enhances ATF7 expression, leading to enhanced cell proliferation and inhibition of apoptosis. Notably, ATF7 is upregulated in HCC tissue, suggesting that HBV may target miR‐340‐5p in vivo to promote ATF7/HSPA1B‐mediated proliferation and apoptosis and regulate liver cancer progression. This work helps to elucidate the complex interactions between HBV and host miRNAs and further suggests that miR‐340‐5p may represent a promising candidate for the development of improved therapeutic strategies for HCC. Abstract : In the present study, we showed that miR‐340‐5p plays an important role during HBV infection and hepatocellular carcinoma development. Specifically, this miRNA directly binds to the mRNA encoding activating transcription factor 7 (ATF7), a protein that both promotes cell proliferation and suppresses apoptosis through its interaction with heat shock protein A member 1B (HSPA1B). We further found that miR‐340‐5p is downregulated by HBV, which enhances ATF7 expression, leading to enhanced cell proliferation and inhibition of apoptosis. Notably, ATF7 is upregulated in HCC tissue, suggesting that HBV may target miR‐340‐5p in vivo to promote ATF7/HSPA1B‐mediated proliferation and apoptosis and regulate liver cancer progression.